Emerging infection: streptococcal toxic shock-like syndrome caused by group B Streptococcus (GBS), Streptococcus agalactiae - Fareed Rajack; Shawn Medford; Ali Ramadan; Tammey Naab (University of São Paulo, 2024)
Streptococcus agalactiae or Group B Streptococcus (GBS) infections are commonly associated with infections in neonates and pregnant women. However, there has been a rising incidence in nonpregnant adults. The risk of GBS infection in nonpregnant adults is increased for patients of advanced age and those with underlying medical conditions such as diabetes mellitus and cancer. We present a 77-year-old female with type-2 diabetes mellitus, hypertension, and bilateral foot ulcers that presented in probable septic shock with necrotic foot ulcers and necrotizing fasciitis and underwent bilateral lower limb amputations. The patient fulfilled the Streptococcal Toxic Shock Syndrome (STSS) criteria as defined by The Working Group on Severe Streptococcal Infections. These criteria were created for group A Streptococcus (Streptococcus pyogenes). Our patient fulfilled the Working Group's criteria, except that the blood culture was positive for group B Streptococcus (Streptococcus agalactiae). Numerous studies demonstrate the importance of early detection and antibiotic treatment for GBS infections in general and early surgical management for necrotizing soft tissue infections (NSTIs) such as necrotizing fasciitis.